1984
DOI: 10.1152/ajprenal.1984.246.5.f656
|View full text |Cite
|
Sign up to set email alerts
|

Steroid regulation of Na+-K+-ATPase: differential sensitivities along the nephron

Abstract: Steroid hormonal activation of the Na+-K+-ATPase enzyme was examined in enriched preparations of outer medullary collecting tubules (MCT) and outer medullary thick ascending limbs of the loop of Henle (MAL), prepared by sedimentation through a discontinuous Ficoll gradient. Using morphological criteria, there was a 2.9-fold enrichment of MCT in fraction 1 when compared with fraction 2 and a 2.2-fold enrichment of MAL in fraction 2 when compared with fraction 1. This separation was further defined using biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…There is considerable evidence that glucocorticoids increase renal Na-K ATPase activity (25)(26)(27)) and membrane area (1). However, in all of these studies (1,(25)(26)(27), pharmacological doses of glucocorticoids were employed. It is likely, therefore, that the alterations in ultrastructure and ATPase activity in these previous studies resulted, in large part, from nonspecific binding to mineralocorticoid receptors in the cortical collecting tubule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable evidence that glucocorticoids increase renal Na-K ATPase activity (25)(26)(27)) and membrane area (1). However, in all of these studies (1,(25)(26)(27), pharmacological doses of glucocorticoids were employed. It is likely, therefore, that the alterations in ultrastructure and ATPase activity in these previous studies resulted, in large part, from nonspecific binding to mineralocorticoid receptors in the cortical collecting tubule.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is substantiated by the fact that spironolactone, a competitive inhibitor of mineralocorticoids, interferes with the dexamethasone-induced stimulation of ATPase (24). Furthermore, low physiological doses of glucocorticoid have been shown not to have an effect on ATPase activity in the cortical collecting tubule (9,23,26). It is also likely that the effects of dexamethasone on ATPase in renal homogenates (25)(26)(27) represent an effect on the proximal tubule and loop of Henle, nephron segments that have glucocorticoid receptors (24,26,28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, both aldosterone-specific (37) and dexamethasone-specific (36,38,39) binding sites have been identified in the mTALH using autoradiography and classic binding techniques. In addition, a number of laboratories (13,(40)(41)(42) have reported that Na-K-ATPase activity in the rat mTALH is reduced by 25-50% after adrenalectomy. However, it is unclear whether this effect of adrenalectomy is due to loss of type I receptor effects or type II receptor effects, since either aldosterone (42) or dexamethasone (40,41) has been shown to restore Na-K-ATPase activity to normal or near normal in the mTALH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of laboratories (13,(40)(41)(42) have reported that Na-K-ATPase activity in the rat mTALH is reduced by 25-50% after adrenalectomy. However, it is unclear whether this effect of adrenalectomy is due to loss of type I receptor effects or type II receptor effects, since either aldosterone (42) or dexamethasone (40,41) has been shown to restore Na-K-ATPase activity to normal or near normal in the mTALH. Moreover, Marver and co-workers (16, 36) observed a 42% reduction in the activity of another enzyme, citrate synthase (a putative marker of mineralocorticoid action), in the rabbit mTALH following adrenalectomy, and demonstrated that the activity of this enzyme could be restored to normal with aldosterone, but not dexamethasone, administration.…”
Section: Discussionmentioning
confidence: 99%